SARANA DAN PRASARANA PENDIDIKAN DALAM PENINGKATAN KUALITAS PEROSES BELAJAR SISWA - Suyono Suyono; Ade Nur Triyani; Camelia Camelia; Novi Wulandari Purba (Jurnal Administrasi Pendidikan, 2022)
This study aims to explain how the situation and condition of educational facilities and infrastructure in improving the quality of student learning processes in MTs Darul Ilmi. This study uses a qualitative approach through data collection, observation, and interviews. In this study the results obtained regarding (1) Facilities and infrastructure at MTs Darul Ilmi; (2) Status of existing facilities and infrastructure on Mount Darul Ilmi; (3). The school manages existing facilities and infrastructure; and (4). Well-developed facilities and infrastructure can improve the quality of students at MTs Darul Ilmi. In the process of implementing teaching and learning there are several things that cannot be separated from the process, namely facilities and infrastructure. Facilities and infrastructure are the most important things to support the teaching and learning process. The existence of good and well-established facilities and infrastructure is a supporting factor in this matter. Perfect facilities and infrastructure make the teaching and learning process in schools run smoothly, and it is easier for students to accept the knowledge taught by the teacher. Good management of facilities and infrastructure is one of the factors in improving the quality of school education.